Cultivating Cultural and Language Interest among Youth through a Local Wisdom-Based Arabic Language Learning Program - Joko Setiono; Biqi Zain (Institut Studi Islam Muhammadiyah Pacitan, 2025)
This study aims to assess the effectiveness of a local wisdom-based Arabic language learning program in fostering learning interest, language proficiency, and cultural awareness among adolescents in Kembang Village, Pacitan. The program was designed by integrating local cultural elements, such as folklore, proverbs, traditional rituals, and traditions, into Arabic language learning activities. The research method used was classroom action research (CAR) with qualitative and quantitative approaches. Data were collected through observation, in-depth interviews, language proficiency tests, and documentation of participant activities. The results showed that the program significantly increased interest in learning Arabic among adolescents, as evidenced by participants’ active participation in activities, enthusiasm in discussions, and high intrinsic motivation. Participants’ Arabic language competencies, including vocabulary, grammar, and speaking and listening skills, improved through a contextual approach that linked language to local culture. Furthermore, the program encouraged active participation, creativity, and collaboration, enabling adolescents to express themselves through drama, poetry, and short stories. A broader impact was seen in the formation of cultural identity, where participants gained a greater appreciation and understanding of local values ​​and saw language proficiency as a means to preserve cultural heritage. The findings of this study confirm that local wisdom-based Arabic language learning is not only effective in improving language skills but also in strengthening participants’ cultural awareness and character. The study recommends implementing this model more widely and providing training to teachers to creatively integrate language and culture, so that the program can be sustainable and have a broader positive impact on the younger generation.